2013
DOI: 10.1186/1475-925x-12-51
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis and processing methods in verifying the correctness of performing low-invasive esthetic medical procedures

Abstract: BackgroundEfficacy and safety of various treatments using fractional laser or radiofrequency depend, to a large extent, on precise movement of equipment head across the patient’s skin. In addition, they both depend on uniform distribution of emitted pulses throughout the treated skin area. The pulses should be closely adjacent but they should not overlap. Pulse overlapping results in amplification of irradiation dose and carries the danger of unwanted effects.MethodsImages obtained in infrared mode (Flir SC520… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The initial image acquisition performed with a camera confirmed that the size of a single cluster of noise is not greater than 4 pixels. Therefore, the sufficient mask size was M h × N h = 9 × 9 pixels [ 26 ]. The filtered sequence of images L MED ( m,n,s,i ) was further subjected to stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…The initial image acquisition performed with a camera confirmed that the size of a single cluster of noise is not greater than 4 pixels. Therefore, the sufficient mask size was M h × N h = 9 × 9 pixels [ 26 ]. The filtered sequence of images L MED ( m,n,s,i ) was further subjected to stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned before, thermal parameters like active time are the ones dominating laser-skin interaction in port wine stain's treatment. Works that implement thermal vision to analyze the skin treatment process can be found, as in [13][14][15] (those works are focused on area temperature observing), or to detect the presence of vascular disorders as in. 16 Our method is targeted toward the laser treatment itself, and it implements accurate single beam tracking assuming considerable movements that would translate the laser beam within the camera field of view during the treatment.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…If the maximum number of a single distortion is not greater than 4 pixels, the optimum mask size is M h × N h = 3 × 3 pixels. In practice, the most common choice of the median filter is mainly due to the fact that it does not introduce new temperature values ​​for the analysed pixels. The filtered input image L GRAY ( m,n ) results in the image L MED ( m , n ).…”
Section: Methodsmentioning
confidence: 99%